Breaking the Barriers in Resident Education: A Quality Improvement Initiative. Issue 4 (July 2018) - Cabarga, Larissa H.; Cubeddu, Luigi X.; Olickal, Jiny; Habibnejad, Samira; Kury-Perez, Elizabeth; Pundhir, Pooja; Pirela, Daniela; Goldszer, Robert C.
Abstract : Introduction: In 2013, the American College of Cardiology and American Heart Association updated the cholesterol guideline. Despite strong evidence supporting the recommendations, a discernible gap exists in the number of residents who practice them. Our study aimed to identify barriers hindering residents from guideline implementation. Methods: Twenty eight residents were administered a preintervention and postintervention questionnaire to identify barriers in guideline application. The questionnaire was categorized into three barriers: knowledge, attitude, and behavior. A multifaceted educational intervention consisting of directed teaching sessions and supervised patient encounters was conducted. Results: Our analysis showed that our residents lacked awareness, familiarity, and self-efficacy in using the cholesterol guideline. The intervention led to significant improvements in awareness (79% vs. 43%, p = .0129), familiarity (61% vs. 29%, p = .0306), and self-efficacy (65% vs. 16%, p = .0018) and achieved a 31% increase in knowledge ( p = .0001), 38% in attitude ( p = .0001), and 20% in behavior ( p = .019). The overall improvement in scores averaged 30% ( p = .0001). Conclusion: Our quality improvement initiative successfully improved our resident's comprehension and applicability of the 2013 ACC/AHA cholesterol guideline. We recommend a multifaceted educational approach tailored toward addressing specific barriers to improve the practice of evidence-based medicine. Abstract : Supplemental Digital Content is Available in the Text.